Antibiotic literacy among Japanese medical students. Issue 10 (October 2020) - Hagiya, Hideharu; Ino, Hideo; Tokumasu, Kazuki; Ogawa, Hiroko; Miyoshi, Tomoko; Ochi, Kanako; Otsuka, Fumio
Abstract: Antimicrobial resistance (AMR) is an urgent global issue. After the AMR action plan was introduced in 2016, a study on antibiotic literacy (i.e., awareness, knowledge, and attitude relating to antimicrobial use) among clinicians and lay people was conducted in Japan. However, no studies have hitherto targeted medical students who are expected to have a high level of antibiotic literacy. The present study was conducted between September 2019 and February 2020, enrolling undergraduate students at Okayama University Medical School. We collected data using a paper-based questionnaire form with 11 questions about antibiotic literacy. The response rate was 93.8% (661/705 students). Overall, 92.6% of the students knew that antibiotics inhibit the growth of bacteria. Student reporting that antibiotics could treat the common cold accounted for 77.0% (Year 1), 50.9% (Year 2), 48.2% (Year 3), 49.1% (Year 4), 23.8% (Year 5), and 26.2% (Year 6). Only 43 (6.5%) had heard about the AMR action plan. The study data suggested that medical students' level of literacy on antimicrobial use should be further enhanced to address AMR and promote antimicrobial stewardship.